1995
DOI: 10.1093/jac/36.4.657
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dose pharmacokinetics of an oral solution of itraconazole in patients receiving chemotherapy for acute myeloid leukaemia

Abstract: The multiple dose pharmacokinetics of a solution of itraconazole given orally were measured in an open study of 20 patients undergoing remission induction chemotherapy for acute myeloid leukaemia. Patients were given itraconazole 5 mg/kg od, 2.5 mg/kg bd, 2.5 mg/kg od or 1.25 mg/kg bd. The mean daily dose of itraconazole was 407 mg for patients receiving 5 mg/kg/day and 148 mg in patients receiving 2.5 mg/kg/day. Mean concentrations of 493 and 495 micrograms/L were achieved on day 8 in patients who received 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 9 publications
5
51
1
Order By: Relevance
“…Similar results to those obtained in autologous recipients were observed in patients receiving chemotherapy for acute myeloid leukaemia. 13 We have previously found 14 that itraconazole doses of 600 mg daily as capsules were needed to achieve a therapeutic level in neutropenic patients, including autologous BMT patients receiving no TBI during conditioning, with C min of itraconazole measured after 6 days of treatment comparable to those observed in our present trial with 400 mg daily oral solution formulation. After 9 days of treatment at a 400 mg dosage, we observed with the oral solution 72% of patients achieving a satisfactory level of unchanged ITRA vs, in our previous study, 55% (five out of nine patients) with the capsule formulation.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results to those obtained in autologous recipients were observed in patients receiving chemotherapy for acute myeloid leukaemia. 13 We have previously found 14 that itraconazole doses of 600 mg daily as capsules were needed to achieve a therapeutic level in neutropenic patients, including autologous BMT patients receiving no TBI during conditioning, with C min of itraconazole measured after 6 days of treatment comparable to those observed in our present trial with 400 mg daily oral solution formulation. After 9 days of treatment at a 400 mg dosage, we observed with the oral solution 72% of patients achieving a satisfactory level of unchanged ITRA vs, in our previous study, 55% (five out of nine patients) with the capsule formulation.…”
Section: Discussionsupporting
confidence: 77%
“…Use of the itraconazole cyclodextrin solution may help to overcome this difficulty. 24,25 The rate of positive surveillance cultures did not decline in period 2 despite the fact that there were less fatal fungal infections. Itraconazole does not reach effective concentrations in the mucosa of the gastrointestinal tract and is found in low concentrations in the saliva.…”
Section: Discussionmentioning
confidence: 97%
“…10,11 A recent study in neutropenic children suggests that higher plasma concentrations may be achieved than in adults (mean concentrations Ͼ250 ng/ml were achieved after 3 days in 6-14-year-olds and after 5 days in children under 5 who received 5 mg/kg/day of itraconazole oral solution 19 ). An earlier study had found that plasma levels Ͻ250 ng/ml were associated with prophylaxis failure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Itraconazole has a broader spectrum of activity and is active against both Candida and Aspergillus 7 but the capsule formulation has unpredictable absorption, 8,9 is inconvenient to administer to young children and may be difficult for patients with mucositis to swallow. An oral solution of itraconazole with better bioavailability than the capsules 10,11 is now available and has recently been licensed for use as prophylaxis against deep fungal infections in adult patients with neutropenia. Results from a randomised study in adult neutropenic patients suggest that itraconazole solution provides greater protection than fluconazole against fatal Aspergillus infection.…”
mentioning
confidence: 99%